1992
DOI: 10.1007/bf03008305
|View full text |Cite
|
Sign up to set email alerts
|

Double aortic arch presenting as massive haematemesis after removal of a nasogastric tube

Abstract: CANADIAN JOURNAL OF ANAESTHESIA patients required medical attention for their headache. Backache was reported more frequently following SAB (14 patients) than general anaesthesia (five patients). Nausea or vomiting was twice as common after general anaesthesia as SAB and was more frequent following discharge (18 cases) than in the recovery room (seven cases). The mean duration of anaesthesia was longer for the group receiving SAB, 52-12 minutes, compared to 45 ___ 15 min for the group receiving general anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…AEF that is caused by intubation into the esophagus is reported to be a fatal complication in DAA patients [1,2,3,4,5,6,7,8,9], although only 1 case has been reported in adults [1]. As both an inserted tube and the vascular ring together compress the esophageal wall, necrosis and ulceration develop and often result in AEF accompanied with massive hematemesis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEF that is caused by intubation into the esophagus is reported to be a fatal complication in DAA patients [1,2,3,4,5,6,7,8,9], although only 1 case has been reported in adults [1]. As both an inserted tube and the vascular ring together compress the esophageal wall, necrosis and ulceration develop and often result in AEF accompanied with massive hematemesis [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is useful in feeding, drainage, etc. But the combination of nasogastric tube and double aortic arch (DAA), a rare congenital vascular abnormality, is known to cause fatal aortoesophageal fistula (AEF) [1,2,3,4,5,6,7,8,9]. Moreover, DAA had never been reported as a cause of superior mesenteric artery (SMA) syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of aortoesophageal fistula development in adult patients with congenital aortic arch abnormalities and prolonged nasogastric intubation has been previously reported. An extensive literature review showed an abundance of cases of congenital aortic arch abnormalities, including double aortic arch, and aortoesophageal fistula in the setting of prolonged nasogastric intubation in the pediatric population [4][5][6][7][8][9][10][11] , but only a few in the adult patient population [12][13][14][15][16][17][18] (Tables 1 and 2). …”
Section: Discussionmentioning
confidence: 99%
“…Particular care must be taken during preoperative evaluation of esophageal carcinoma. Indeed, tracheal or esophageal endoscopy, biopsy or intubation can lead to iatrogenic aortotracheal or aortoesophageal fistula with consequent massive, lethal bleeding 15 . Furthermore, preoperative evaluation must include cardiac ultrasonography to detect associated latent heart malformation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tracheal or esophageal endoscopy, biopsy or intubation can lead to iatrogenic aortotracheal or aortoesophageal ®stula with consequent massive, lethal bleeding. 15 Furthermore, preoperative evaluation must include cardiac ultrasonography to detect associated latent heart malformation. 9 Esophageal resection, lymph node removal and gastroesophageal anastomosis cannot be performed through a right thoracotomy in cases of RAA, and therefore a left thoracotomy is required.…”
Section: Discussionmentioning
confidence: 99%